A mixed-methods evaluation of an intervention for enhancing alcohol screening in adults aged 50+ attending primary health care. - Towers, Andy; Newcombe, David; White, Gillian; McMenamin, John; Sheridan, Janie; Rahman, Juma; Moore, Alison (Journal of Primary Health Care, 2025)
Introduction: Adults aged 50 years and over are drinking more than ever but primary health care (PHC) professionals find it challenging to screen them for alcohol-related harm, despite being at greater risk for harm than younger drinkers. Aim: This intervention aimed to enhance alcohol screening for this cohort by (a) introducing an algorithm in the patient management system to automate detection of alcohol risk in patients and (b) providing training to support health professionals' practice of, knowledge about, and comfort with alcohol screening in this cohort. Methods: Eleven PHC practices in Aotearoa New Zealand took part in this intervention, including 41 PHC health professionals. Development and integration of the automated alcohol screening process within PHC patient management systems was undertaken in parallel with health professional training approaches. Results: Screening rates increased substantially at intervention initiation but fell immediately with the onset of the New Zealand COVID-19 national lockdown. Two-thirds of health professionals identified the system screening prompts, over 40% felt this changed their screening practice, and 33% increased their awareness of – and felt more comfortable screening for – alcohol-related risk in those aged 50+. Discussion: We illustrated an initial increase in alcohol screening rates in those aged 50+ as a result of this intervention, but this increase could not be sustained in part due to COVID-19 disruption. However, health professionals indicated that this intervention helped many change their practice and enhanced their awareness of such risk and comfort in screening for alcohol-related risk in those aged 50+. What is already known: Hazardous alcohol use is increasing substantially in older adults, yet they are less likely than younger adults to be screened for alcohol use and related harms in primary health care. What this study adds: This research demonstrates the acceptability and value in an approach to identifying alcohol-related harm in those aged 50+ that combines the knowledge of primary health care professionals about alcohol-related harm in this cohort and the use of existing electronic health records to automate detection of risk factors.